Characterization and modification of waste magnesium chip utilized as an Mg-rich intermetallic composite - Figen, Aysel Kanturk; Piskin, Sabriye (ELSEVIER SCIENCE INC, 2014)
In this study, the characterization and modification of waste magnesium chips (WMCs), which were produced by plastic molding in a gold manufacturing factory and are used as Mg-rich intermetallic composites in storing hydrogen, were discussed in detail. WMCs were analyzed using X-ray diffraction (XRD), X-ray fluorescence (XRF) spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) analysis to characterize the materials' structural properties. Mechanical milling, organic treatment, and inorganic salt addition were carried out to modify the WMCs' surface to prepare Mg-rich intermetallic composites for storing hydrogen. The modified samples were analyzed using high-pressure volumetric analyses to calculate their hydrogen storage capacity. The authors conclude that modified WMC was promising as an Mg-rich intermetallic composite that was suitable for use in hydrogen storage with a 4.59 wt% capacity at 320 degrees C under a hydrogen pressure of 60 bar. (C) 2014 Published by Elsevier B.V. on behalf of Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.
Keywords: Waste magnesium chip; Characterization; Modification; Hydrogen storage; Intermetallic composite; HYDROGEN SORPTION PROPERTIES; NANOCRYSTALLINE MG; STORAGE PROPERTIES; GRAPHITE; METALS; CARBON; Engineering; Materials Science